Cost Effectiveness Analysis (CEA) of Antihypertensives Use in Inpatient Hemodialysis Patients at Abdoel Wahab Sjahranie Hospital Samarinda - Sri Setianingsih, Diah; Nur Chairin Hanifa, Deasy (Media Farmasi: Jurnal Ilmu Farmasi, 2025)
Hypertension is the first comorbid disease that can occur in patients with damaged kidney function. Apart from that, hypertension is a complicating disease that often occurs during the hemodialysis process.  The large variations in the use of antihypertensives in patients with chronic renal failure on hemodialysis therapy can affect the cost incurred by these patients. The purpose of this study was to optimize the use of the most cost-effective and pharmacological antihypertensive drugs in patients undergoing hemodialysis therapy. This research is a descriptive study with a pharmacoeconomic approach using the Cost Effectiveness Analysis (CEA) method. The measurement indices used to analyze the data are ACER and ICER. Data collection was conducted retrospectively, taken from the medical records of inpatient hemodialysis patients by reviewing the inclusion data of patients who were eligible to be research objects. Direct medical costs were taken from the average cost of hemodialysis, other procedures, room costs and drug costs. The effectiveness of drug therapy was determined based on the Mean Arterial Pressure (MAP) value that met the normal value. Research data is grouped based on therapy patterns and then analyzed to obtain cost – effective therapy. The results of the study showed that the percentage effectiveness of antihypertensive therapy with Furosemide was 46%, the combination of Amlodipine and Candesartan was 69% and the combination of Furosemide, Amlodipine, and Candesartan was 56%. Based on the ACER value of Rp. 1,726,133.4, the combination of antihypertensive Amlodipine and Candesartan is the most cost-effective therapy option and based on the ICER value of Rp. -6,697,330.3, the combination of antihypertensive Amlodipine and Candesartan is also the most cost-effective therapy option.